Quantifying maternally derived respiratory syncytial virus specific neutralising antibodies in a birth cohort from coastal Kenya. Issue 15 (8th April 2015) - Nyiro, Joyce U.; Sande, Charles; Mutunga, Martin; Kiyuka, Patience K.; Munywoki, Patrick K.; Scott, J. Anthony G.; Nokes, D James
Highlights We report on the characteristics of RSV neutralising antibodies in a birth cohort. The levels of cord RSV antibodies increase during seasonal virus transmission. The rate of decay of RSV antibodies following birth is independent of cord titre. There is a high degree of variation between individuals in rate of decay. Important baseline data to maternal RSV vaccine development are provided.